Modificação a plasma de compósitos a base de celulose bacteriana e fosfato de prata - Generoso, Amanda (2024)
The recent of coronavirus pandemic (COVID-19) highlighted the problem of emerging microbial infections in the current public health scenario, which are often difficult or even impossible to treat. In this context, there is a demand for the development of advanced materials that inactivate microorganisms aiming at the protection of the human population. Bacterial Cellulose (BC) is a natural polymer, which has high mechanical resistance, high water retention capacity, high crystallinity, and thermal stability. It also has the advantages of being biocompatible, non-toxic, and biodegradable. The architecture of the BC is composed of nanofibers with high porosity, which contribute to modifications and incorporation of substances in its matrix to improve or add properties and expanding its applicability. Despite its excellent characteristics, BC in its natural form does not present antimicrobial activity, therefore, many scientists have dedicated themselves to researching methods to add this property and expand the applicability of this biopolymer. Recent studies demonstrate that semiconductor materials, such as silver phosphate (Ag3PO4), have high biocidal potential against bacteria, fungi, and viruses. In that regard, this work proposed to synthesize BC/Ag3PO4 composite films using a vacuum filtration system for the formation and immobilization of Ag3PO4 crystals in the BC matrix, developing a material with better physicochemical properties, biocompatible, non-toxic and with antimicrobial properties. Additionally, the composite films were modified by oxygen plasma etching, to promote the exposure of Ag3PO4 microparticles incorporated into the biopolymer, intensifying the material's antimicrobial effect. The micrographs of the BC/Ag3PO4 composites obtained by SEM confirmed the presence of dispersed microparticles and agglomerates distributed throughout the entire length of the polymeric matrix. Furthermore, a cell cytotoxicity assay was carried out, which attested to cell viability above 70% for pure BC films as well as for BC/Ag3PO4 composites. Analyses carried out after oxygen plasma treatment indicate an increase in the hydrophilicity of pure BC films and BC/Ag3PO4 composites due to the incorporation of oxygenated functional groups in the material.